The Impact of Product Quality, Customer Service, and Brand Image on Customer Loyalty - Jailos, Herry Mgalilwa; Magasi, Chacha (International Review of Management and Marketing, 2025)
Grounded in the Relationship Marketing Theory, the study examines the role of product quality, customer service, and brand image in fostering long- term customer loyalty. The study utilized a simple random sampling technique to collect quantitative data from 285 customers. Correlational research design and multiple linear regression were employed to examine relationships among key variables. The findings indicate that strong brand image (β3 = 0.617, P < 0.001), perceived superior product quality (β1 = 0.252, P = 0.001) and effective customer service (β2 = 0.173, P = 0.012), all have a strong significant positive influence on customer loyalty respectively. The findings show that a strong brand image, perceived superior product quality, and effective customer service are decisive factors in fostering customer loyalty in the iron roofing industry, with brand image exerting the most substantial influence. The implication is that businesses should prioritize strategic branding, high-quality products, and exceptional service to secure long-term consumer commitment and competitive advantage. It is recommended that iron sheets manufacturing firms formulate, plan and invest in marketing strategies which substantially capitalize in producing superior quality roofing iron sheets, enhance exceptional reputable brand image and responsive customer service. This study introduces a novel framework linking brand reputation factors and customer loyalty.